2020
DOI: 10.1021/acsinfecdis.9b00492
|View full text |Cite
|
Sign up to set email alerts
|

The Nonstructural Protein of Guertu Virus Disrupts Host Defenses by Blocking Antiviral Interferon Induction and Action

Abstract: Guertu virus (GTV) is a potentially highly pathogenic bunyavirus newly isolated in China, which is genetically related to the severe fever with thrombocytopenia syndrome virus (SFTSV) and Heartland virus (HRTV), two other emerging life-threatening bunyaviruses. Previous studies suggested that SFTSV and HRTV antagonize the interferon (IFN) system by targeting antiviral signaling proteins in different ways. However, whether and how GTV counteracts the host innate immunity are unclear. Here, we found that GTV str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…EGFPfused N or N-arm expression plasmids were constructed using the pEGFP-N1 vector. Expression plasmids for TBK1, SFTSV N or NSs, or HRTV N and the plasmid expressing Renilla luciferase (pRL-TK) were previously described [15,16,18,59]. Expression plasmids for GTV N, SFTSV GP or SFTSV RdRp were similarly constructed by standard molecular biology technique.…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFPfused N or N-arm expression plasmids were constructed using the pEGFP-N1 vector. Expression plasmids for TBK1, SFTSV N or NSs, or HRTV N and the plasmid expressing Renilla luciferase (pRL-TK) were previously described [15,16,18,59]. Expression plasmids for GTV N, SFTSV GP or SFTSV RdRp were similarly constructed by standard molecular biology technique.…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
“…Act.) were then shown by normalization of firefly luciferase activities to Renilla luciferase activities as described previously [15,16,59].…”
Section: Minigenome Assaymentioning
confidence: 99%
“…Moreover, by an ambisense strategy, bandavirus S segment also encodes a non-structural protein (NSs) which is involved in the formation of viral inclusion body and plays important roles at the interface of virus-host interactions ( Yu et al, 2011 ; Ning et al, 2014 ). Particularly, previous studies by us and others have suggested that NSs hijacks several critical host signaling proteins including kinases TANK-binding kinase 1 (TBK1)/IκB kinase ε (IKKε) and transcription factors signal transducer and activator of transcription 1 (STAT1)/STAT2 into the viral inclusion body “jail,” thus blocking interferon (IFN) antiviral immune responses ( Yu et al, 2011 ; Ning et al, 2014 , 2015 , 2017 , 2019 ; Santiago et al, 2014 ; Wu et al, 2014 ; Feng et al, 2019 ; Min et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, little is known about the interactions of these bunyaviruses with their hosts. Interestingly, we recently demonstrated that similar to SFTSV NSs, the NSs proteins of HRTV and GTV can also target the host kinase TBK1 to inhibit RIG-I-and MDA5-mediated antiviral signaling (77,83). This conservative RLR signaling-targeting activity exhibited by the NSs proteins may reflect the general involvement of RLRs in the pathogenesis of these bunyaviruses.…”
Section: Sftsv-host Interactions and Thus Likely Benefiting The Future Development Of Antiviral Therapymentioning
confidence: 99%